The Oral Health Status and Hygiene of the Dependent Elderly in Muang, Phitsanulok, Thailand - Sangouam, Supaporn; Wongsriya, Kietsuda; Ratanadheeradhorn, Sawittree; Channetikit, Awatsada (UI Scholars Hub, 2016)
To assess the oral health status and oral hygiene habits of the dependent elderly in Muang Phitsanulok, Thailand. Methods: 70 dependent elderly with an activity of daily living score of 0 - 4 were selected for this study using a convenience sampling technique. Both participants and their caregivers were interviewed and an oral examination was carried out on all subjects. Information regarding demographics, oral health care habits, and oral health status including dental caries, remaining dentition, and occluding pairs of teeth was collected. The data was analysed using descriptive statistics. Results: Results showed that 82.1% of the participants had at least one carious lesion. 62.9% of subjects possessed their natural dentition, however 52% of those did not have any occluding teeth. The majority of the edentulous group were categorised as a low socioeconomic status. Interestingly, none of the dentate group reported ever flossing their teeth, 31.9% brushed their teeth twice daily, and 14.3% reported that they did not employ any oral hygiene methods. Additionally, it was found that the caregivers played a major role in the oral health care of the dependent elderly. Conclusion: The oral health of the dependent elderly is generally poor, especially amongst the low socioeconomic community. The subject’s declining dexterity and increase of general health risks limits their ability to maintain acceptable oral health.